Talaromyces marneffei infection in a non-HIV non-endemic population. (2018) - Castro-Lainez, Miriams Teresita; Sierra-Hoffman, Miguel; LLompart-Zeno, Juan; Adams, Robin; Howell, Alan; Hoffman-Roberts, Holly; Fader, Robert; Arroliga, Alejandro C.; Jinadatha, Chetan
Abstract: Introduction: Talaromyces marneffei infection is a systemic mycosis, caused by a dimorphic fungus, an opportunistic pathogen formerly known as Penicillium marneffei . This disease is endemic to Southeast Asia and common in human immunodeficiency virus (HIV) infected patients with low CD4 counts. Here we present a very rarely reported case of Talaromyces marneffei infection in an apparent non-immunosuppressed patient presenting decades later in a non-endemic setting (United States). Presentation of case: Our patient was a 75-year-old Caucasian Navy veteran, who served in Vietnam as a part of the Swift Boat service in 1966. He presented to his primary care provider with uncontrolled nonproductive cough and abnormal chest computerized tomography. Bronchoscopy specimens showed Talaromyces . He was empirically treated with itraconazole and then switched to voriconazole after confirmation of diagnosis but he later deteriorated was changed to liposomal amphotericin B and isavuconazole. Patient did well for the next 90 days on isavuconazole until the therapy was stopped. Soon after stopping the medication (isavuconazole) his symptoms recurred and ultimately patient expired. Discussion: Talaromycosis generally presents as pulmonary infection with manifestations similar with other endemic fungi. It is often seen HIV patients with travel to South east Asia. Very rarely this infection is seen and reported in non-immunosuppressed and in non-endemic areas. To date there are 4 well-documented cases among non-HIV, non-endemic population. Conclusion: Talaromyces can cause infection in non-HIV and non-endemic population and could be an underrecognized cause of pulmonary infections among veterans with even a remote history of exposure to the organism during deployment.